2019
DOI: 10.1093/biosci/biz095
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Integrative, Eco-Evolutionary Understanding of Ecological Novelty: Studying and Communicating Interlinked Effects of Global Change

Abstract: Global change has complex eco-evolutionary consequences for organisms and ecosystems, but related concepts (e.g., novel ecosystems) do not cover their full range. Here we propose an umbrella concept of “ecological novelty” comprising (1) a site-specific and (2) an organism-centered, eco-evolutionary perspective. Under this umbrella, complementary options for studying and communicating effects of global change on organisms, ecosystems, and landscapes can be included in a toolbox. This allows researchers to addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 89 publications
0
85
0
Order By: Relevance
“…This study introduced the Biotic Novelty Index (BNI) and demonstrated its applicability as a framework to measure the ecological novelty of communities at different spatial scales. We regard ecological novelty as a continuous gradient ranging from historic or analog to novel (Heger et al . 2019) rather than a binary classification.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study introduced the Biotic Novelty Index (BNI) and demonstrated its applicability as a framework to measure the ecological novelty of communities at different spatial scales. We regard ecological novelty as a continuous gradient ranging from historic or analog to novel (Heger et al . 2019) rather than a binary classification.…”
Section: Discussionmentioning
confidence: 99%
“…We designed the BNI to combine two aspects of ecological novelty: historical novelty, captured by the sequence of arrivals of new species in a given region, and functional novelty contributed by the new species (Heger et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations